2012
DOI: 10.1271/bbb.120279
|View full text |Cite
|
Sign up to set email alerts
|

Folic Acid Fortification Ameliorates Hyperhomocysteinemia Caused by a Vitamin B6-Deficient Diet Supplemented withL-Methionine

Abstract: Vitamin B 6 (B 6 ) deficiency affects homocysteine metabolism, and this leads to hyperhomocysteinemia. In this study, we examined i) the effects of B 6 -deficiency and graduated levels of dietary methionine on homocysteine metabolism, and ii) the effects of fortified folate on homocysteine metabolism. In experiment 1, Wistar male rats were fed a control or a B 6 -deficient diet supplemented with L-methionine at a level of 3, 6, or 9 g/kg of diet for 5 weeks. The resulting plasma homocysteine levels in the B 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…Folic acid supplementation can effectively reduce homocysteine. [15][16][17][18] Thus, theoretically, if elevated homocysteine is a cause of gestational hypertension or preeclampsia, folic acid supplementation during early pregnancy may significantly reduce the risk of these outcomes or may change the distribution of the early-onset cases. However, our large cohort study results did not find a protective effect of folic acid supplementation on gestational hypertension or preeclampsia, and, thus, supports the hypothesis that elevated blood homocysteine during pregnancy may be a consequence or a concomitance rather than a cause of gestational hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Folic acid supplementation can effectively reduce homocysteine. [15][16][17][18] Thus, theoretically, if elevated homocysteine is a cause of gestational hypertension or preeclampsia, folic acid supplementation during early pregnancy may significantly reduce the risk of these outcomes or may change the distribution of the early-onset cases. However, our large cohort study results did not find a protective effect of folic acid supplementation on gestational hypertension or preeclampsia, and, thus, supports the hypothesis that elevated blood homocysteine during pregnancy may be a consequence or a concomitance rather than a cause of gestational hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Hyperhomocysteinemia usually can be corrected by supplementation with folic acid. [15][16][17][18] Thus, a major concern has been raised about whether folic acid supplementation can prevent the occurrence of gestational hypertension or preeclampsia. Three studies from the United States and Canada demonstrated that folic acid-containing multivitamins may greatly reduce the risk of gestational hypertension or preeclampsia.…”
mentioning
confidence: 99%
“…4) However, the role of folate fortification in this amelioration remained unknown. Folate is involved in the re-methylation pathway, in which 5-MTHF is required as a methyl donor.…”
Section: Involvement Of 5-methyltetrahydrofolate In the Amelioration mentioning
confidence: 99%
“…Male Wistar rats, 4 weeks old and weighing 80-100 g, were obtained from Japan SLC (Hamamatsu, Japan). The rats were fed the following experimental diets: an AIN-76 diet-based control diet (C), 4) a B 6 -deficient diet (D), 4) and two kinds of B 6 -deficient folate-enriched diets (5 mg and 20 mg of pteroylmonoglutamic acid/kg of diet) containing either 2.5-or 10-fold the amount of folate compared to the control diet, respectively designated as F2.5 and F10. All the diets contained L-methionine at a dose of 9 g/kg of diet.…”
Section: Involvement Of 5-methyltetrahydrofolate In the Amelioration mentioning
confidence: 99%
See 1 more Smart Citation